PENGARUH PAJAK AIR TANAH DAN PAJAK RESTORAN TERHADAP PENDAPATAN ASLI DAERAH KOTA BANDUNG - Rima Sundari (Universitas Logistik dan Bisnis Internasional, 2026)
As Bandung's financial system and travel sector grow, the possibilities for the city to create its own tax revenue also become greater. The present methods for gathering tax income, mainly from taxes on subsurface water and eateries, still need further refinement. This research is designed to discover how the taxes from eateries and subsurface water will shape Bandung's income produced locally between 2021 and 2024. This study employs a computational method. To gather all earnings information from Bandung, a thorough sampling approach is implemented, managing all earnings data as a complete population. The sample consists of documents about neighborhood earnings and investing spanning 2021 to 2024. The study applied Product Moment correlation analysis, Multiple Linear Regression Analysis, Coefficient of Determination Test, Partial Test (T-test), and simultaneous test (F-test) with IBM SPSS Statistics edition 27 to dissect the data. According to the t-test results, the underground water levy does not notably influence the city's earnings, but the eating place levy does considerably affect it. The f-test consequences reveal that independently sourced income is greatly formed by the underground water levy and the eating place levy when considered jointly. These outcomes imply that levies on eating places are critical for improving independently generated earnings. Nevertheless, fees for underground water necessitate enhanced management and strategic revisions to enhance their effectiveness in this field.